PENGARUH DISIPLIN KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA RUMAH MAKAN AYAM BLENGER PSP TANJUNG DUREN JARTA BARAT - Hofifa; Suwanto (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of work discipline and leadership style on employee performance both partially and simultaneously at the Blenger PSP Tanjung Duren Chicken Restaurant, West Jakarta. This type of research uses associative quantitative methods. The sampling technique used a saturated sample of 52 respondents. Data analysis techniques use data instrument tests, classical assumption tests. Quantitative data analysis techniques use simple linear regression, multiple linear regression, correlation coefficient, correlation of determination. Hypothesis testing using the t test and F test. The results of the analysis show: Work discipline partially has a positive effect on employee performance with a simple linear regression equation Y=3.515 + 0.856 79.9% means that performance is influenced by recovery by 79.9%. This is proven by the t test, which shows that the t value > t table (14.097 > 2.008) is confirmed by the p value < Sig.0.05 or significance < 0.05 (0.001 < 0.05). Leadership style partially has a  positive  effect  on  employee  performance,  shown  by  the  simple  linear regression equation Y = 1,820 + 1,152 amounting to 70.4%. This is proven by the t test, the t value obtained > t table (10.907 > 2.008) and strengthened by the p value < Sig.0.05 or significance value < 0.05 (0.000 < 0.05). The research results of work discipline and leadership style simultaneously have a positive effect on employee performance, shown by the multiple linear regression equation Y = 1.000 + 0.613 X₁ + 0.416 X2. The correlation coefficient value is 0.909, meaning it has a strong level of relationship and the coefficient of determination is 82.8%, meaning that performance is influenced by compensation and work discipline by 82.6%, while the remaining 17.4% is influenced by other factors not researched. This is proven by the hypothesis test results obtained  by the value Fcount  >  Ftable (116.680 > 3.19) and reinforced by the significance value < 0.05 (0.000 < 0.05). Thus it is proven that Ho is rejected and Ha is accepted.